Democratic Republic of Timor-Leste : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that the economy of the Democratic Republic of Timor-Leste remains fragile. Cumulative growth over the last three years was near zero-mainly reflecting the drawdown in the presence of international agencies. Unemployment is high, 40 percent of the population lives below the poverty line, and social indicators are poor. At the same time, human capital remains scarce, physical infrastructure inadequate, and financing opportunities limited. The government is making good progress with the measures necessary to handle its new oil/gas wealth responsibly.